2018
DOI: 10.1002/ncp.10212
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Support During Pediatric Extracorporeal Membrane Oxygenation

Abstract: Providing adequate nutrition to critically ill pediatric patients is essential and positively impacts outcomes. Critically ill infants and children receiving extracorporeal membrane oxygenation (ECMO) therapy are nutritionally vulnerable, yet there are challenges to reliable assessment of nutrition requirements and to the delivery of optimal nutrition in this cohort. In this review of the relevant literature, we present the current evidence and guidelines for the optimal prescription and delivery of nutrition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…The provision of nutrition in children supported on ECMO has proved challenging because of the lack of a feasible method to estimate nutritional requirements, concurrent use of inotropes and concerns for gut ischemic injury, and lack of robust data to guide nutritional practices. This is further compounded by altered energy requirements and metabolic derangements in this critically ill population ( 4 ). Deleterious effects from overfeeding and underfeeding are well-documented.…”
Section: Introductionmentioning
confidence: 99%
“…The provision of nutrition in children supported on ECMO has proved challenging because of the lack of a feasible method to estimate nutritional requirements, concurrent use of inotropes and concerns for gut ischemic injury, and lack of robust data to guide nutritional practices. This is further compounded by altered energy requirements and metabolic derangements in this critically ill population ( 4 ). Deleterious effects from overfeeding and underfeeding are well-documented.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate nutritional support may contribute to improve the prognosis of critically ill children including those on ECMO ( 5 , 9 ). Enteral route is the preferred method to deliver artificial nutrition in PICU since it has multiple advantages ( 18 ), but due to a variety of barriers, parenteral nutrition is often employed as a sole mode of nutrient delivery or as supplementary.…”
Section: Discussionmentioning
confidence: 99%
“…Providing optimal nutrition to critically ill children is also an important aspect of a favorable outcome. There were few nutritional support studies in pediatric patients who received ECMO even though they were nutritionally vulnerable ( 24 , 25 ). A prior retrospective study showed that early enteral feeding was associated with a lower hospital mortality rate ( 25 ).…”
Section: Discussionmentioning
confidence: 99%